Shifting perspectives: From “Epilepsy” to “Cerebroelectric Disorder” - Koh, Seungyon; Pyo, Sung Inn; Jang, Seol; Kim, Gyujin; won Seo, Seung; Huh, Kyun; Kwon, Soon Sun; Young Choi, Jun (Epilepsy and Behavior, 2024)
Background & Objective: Epilepsy has long been associated with stigma and misconceptions. In response, the Korean Epilepsy Society initiated the Epilepsy Renaming project in 2008 to replace the stigmatizing term with a neutral and scientifically grounded name, “cerebroelectric disorder”. This study explores the impact of changing terminology on the public discourse surrounding epilepsy. Methods: Online news articles from distinct time periods (2001–2003, 2011–2014, 2017–2018, and 2020–2022) were analyzed using text data analysis techniques, including Latent Dirichlet Allocation topic modeling, frequency analysis, and sentiment analysis. The inclusion of data from 2017 to 2018 allowed for an examination of discourse trends independent of the COVID-19 pandemic's influence. Correlation of words in each period was visualized via network maps. Migraine was set as control term to highlight changes in perception devoid of significant stigma intervention efforts. Results: The analysis revealed a significant shift in terminology preference, with cerebroelectric disorder gradually replacing epilepsy in news articles. The discourse surrounding epilepsy evolved over time from focusing on healthcare and economic aspects to patient-centered discussions, emphasizing the daily lives of individuals with epilepsy. This shift towards more empathetic and less stigmatized language was contrasted against the discourse on migraine, highlighting the specific impact of the terminological change on epilepsy's perception. Conclusion: The adoption of the neutral term “cerebroelectric disorder” in South Korea has influenced the discourse surrounding epilepsy, leading to more patient-centered discussions and a reduction in stigma. This study highlights the importance of terminology in shaping public perceptions of diseases and suggests that changing terminology can positively impact the understanding and destigmatization of epilepsy.
Keywords: COVID-19; Epilepsy; Humans; Republic of Korea; Social Stigma; Terminology as Topic; Cerebroelectric disorder; Epilepsy; News articles; Stigma; Terminology